Relative level of glucocorticoid and progesterone receptor: implications for immune and reproductive functions in women - Appadoo, Prettysha (Department of Molecular and Cell Biology, 2025)
Background: The glucocorticoid receptor (GR) and progesterone receptor (PR) are very closely related in terms of their amino acid sequence and three-dimensional structure. PR ligands have been previously reported to cross-react with the GR. The cross-talk effects of certain PR ligands via the GR may impact immune function and risk of acquiring sexually transmitted infections (STIs). This suggests that GR and PR expression levels are relevant to immunity against pathogens in the female genital tract (FGT) and systemic immunity. PR protein expression is well characterised ex vivo in FGT tissues while very little is known about GR protein expression ex vivo in the FGT. Immune cells patrol the FGT but the expression of GR as well as PR proteins in resident immune cells of the FGT has not been previously reported. Aims and Hypotheses: This study aims to assess potential cross-reactivity of GR and PR primary antibodies as it is hypothesised that the antibodies exhibit cross-receptor binding, confounding data interpretation. Another aim is to evaluate GR and PR protein expression in FGT epithelial and stromal cells, with the hypothesis that both GR and PR proteins are expressed in FGT epithelial and stromal cells. The study also seeks to determine and compare GR and PR expression in FGT-resident CD4+ and CD8+ immune cells, hypothesising that these cells express more GR than PR proteins. Finally, the study aims to determine and compare GR and PR protein expression in systemic immune cells, hypothesising that systemic CD3+, CD4+, and CD8+ T lymphocytes, as well as CD14+ monocytes, express higher levels of GR than PR. Models and methodologies: PR-negative COS1 cells overexpressing exogenous GR or PR proteins were used to assess cross-reactivity of primary antibodies by western blot analysis, immunofluorescence staining and flow cytometry. FGT ectocervical tissue explants were used as a model for the FGT. These were stained by immunofluorescence for GR and PR as well as for CD4+ and CD8+ markers. Immunofluorescence staining in ectocervical tissue samples was visualised by confocal microscopy. Peripheral blood mononuclear cells (PBMCs) were used as a model to investigate protein expression levels of GR and PR in systemic CD3+, CD4+, CD8+ and CD14+ cells by flow cytometry. Results: Western blotting, immunofluorescence staining and flow cytometry in COS1 cells overexpressing GR and/or PR confirmed that the anti-GR antibodies did not cross-react with PR proteins and the anti-PR antibodies did not cross-react with GR proteins. Confocal imaging of ectocervical tissue sections demonstrated relatively high levels of expression of GR in epithelial cells, whereas PR expression was predominantly observed in stromal cells. GR was also expressed in some, but not all, FGT CD4+ and CD8+ cells. In contrast, PR fluorescence was absent in CD4+ and CD8+ cells within the FGT. Additionally, no notable trend was observed in GR expression density, PR expression density and the relative expression density of GR versus PR between CD4+ and CD8+ cells. Flow cytometric analysis of PBMCs revealed a high frequency of GR+ cells among the systemic immune cells including CD3+, CD4+ and CD8+ T cells, with significantly lower frequency of CD14+GR+ cells. There was no significant difference in the expression density of GR among systemic CD3+, CD4+, CD8+, and CD14+ cells. Conversely, PR detection in systemic CD3+, CD4+, CD8+, and CD14+ cells was problematic due to non-specific signals and gating challenges. After adjusting for these issues with appropriate controls and gating strategies, flow cytometry data indicated a lack of PR protein expression in systemic CD3+, CD4+, CD8+, and CD14+ cells. Conclusion: The lack of cross-reactivity of GR and PR primary antibodies ensures the reliability of antibody-based protein detection assays employed in the thesis. The widespread expression of GR across different FGT cells, including epithelial, stromal and specific T lymphocytes as well as systemic T lymphocytes and monocytes, signifies its diverse roles throughout the body. These findings suggest a pivotal role of GR in cells regulating FGT barrier function and systemic immunity. In contrast to the GR, PR expression is more restricted and is primarily found in FGT stromal cells. Its presence in FGT epithelial cells is minimal and absent in FGT and systemic T lymphocytes and/or monocytes. The limited expression of PR compared to GR suggests that certain progestogens, such as progesterone and medroxyprogesterone acetate (MPA), may exert off-target effects through the GR in cells crucial for women's immune and reproductive systems. Collectively these findings provide insights on the potential implications of progestins-based hormonal contraceptives (HCs) such as depot MPA (DMPA) for women's health.